Does neoadjuvant chemotherapy plus cytoreductive surgery improve survival rates in patients with advanced epithelial ovarian cancer compared with cytoreductive surgery alone? - Solmaz, Ulas; Mat, Emre; Dereli, Murat Levent; Turan, Volkan; Peker, Nuri; Tosun, Gokhan; Yildirim, Yusuf (Imprimatur Publications, 2015)
Purpose: To compare the outcomes of interval debulking surgery (IDS) after neoadjuvant chemotherapy (NAC/IDS) with primary debulking surgery (PDS) in patients diagnosed with advanced epithelial ovarian cancer (EOC). Methods: A total of 292 patients with stages IIIC and IV disease who were treated with either NAC/IDS or PDS between 1995 and 2012 were retrospectively reviewed. The study population was divided into two groups: the NAC/ IDS group (N=84) and the PDS group (N=208). Progression-free survival (PFS), overall survival (OS), and optimal cytoreduction were compared. Results: The mean age was significantly higher in the NAC/IDS group (61.5 +/- 11.5 vs 57.8 +/- 11.1 years, p=0.01). Optimal cytoreduction was achieved in 34.5% (29/84) of the patients in the NAC/IDS group and in 32.2% (69/208) in the PDS group (p =0.825). The survival rates were comparable. The mean survival rate of patients who achieved optimal cytoreductive surgery in either the PDS or the NAC/ IDS arm was significantly higher than that of patients who achieved suboptimal cytoreductive surgery (p<0.001 and p<0.001, respectively). Multivariate analysis confirmed the treatment method, amount of ascitic fluid, and optimal cytoreduction as independent factors for OS. Conclusions: No definitive evidence was noticed regarding whether NAC/IDS increases survival compared with PDS. NAC should be reserved for patients who cannot tolerate PDS or when optimal cytoreduction is not feasible.
Keywords: debulking surgery; neoadjuvant chemotherapy; ovarian cancer; primary; survival